66b-5=33b+5

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

66⋅(b+5)=(b-5)⋅33

Simplify 66⋅(b+5).

Apply the distributive property.

66b+66⋅5=(b-5)⋅33

Multiply 66 by 5.

66b+330=(b-5)⋅33

66b+330=(b-5)⋅33

Simplify (b-5)⋅33.

Apply the distributive property.

66b+330=b⋅33-5⋅33

Simplify the expression.

Move 33 to the left of b.

66b+330=33⋅b-5⋅33

Multiply -5 by 33.

66b+330=33b-165

66b+330=33b-165

66b+330=33b-165

Move all terms containing b to the left side of the equation.

Subtract 33b from both sides of the equation.

66b+330-33b=-165

Subtract 33b from 66b.

33b+330=-165

33b+330=-165

Move all terms not containing b to the right side of the equation.

Subtract 330 from both sides of the equation.

33b=-165-330

Subtract 330 from -165.

33b=-495

33b=-495

Divide each term by 33 and simplify.

Divide each term in 33b=-495 by 33.

33b33=-49533

Cancel the common factor of 33.

Cancel the common factor.

33b33=-49533

Divide b by 1.

b=-49533

b=-49533

Divide -495 by 33.

b=-15

b=-15

b=-15

Solve for b 66/(b-5)=33/(b+5)